PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT ASTRA INTERNATIONAL TBK PERIODE 2011 - 2022 - ova Santika Dewi, Mutiara N; Mardiana, Sri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio on Return On Assets at PT Astra International Tbk for the 2011 - 2022 period. The population in this research is the financial report of PT Astra International Tbk. The sample used is the financial report, namely the balance sheet and profit and loss report of PT Astra International Tbk for the 2011-2022 period. The nature of the research used is quantitative asosiative. The data analysis methods used include classical assumption tests, multiple regression equations, coefficient of determination, correlation coefficient tests and hypothesis tests. Based on the research results, the Current Ratio has no significant effect on Return On Assets, showing the test results tcount = -0,352 while ttable = 1,812 (tcount < ttable) with a significance level of 0,002 < 0,05, then the Debt to Equity Ratio has a significant effect on Return On Assets shows the test results tcount = 2,290 while ttable = 1,812 (tcount > ttable) with a significance level of 0,045 < 0,05. The F test shows that the results of the Current Ratio and Debt to Equity Ratio have a significant and significant effect on Return On Assets with test results of Fcount = 4,534 and Ftable = 4,46 (Fcount > Ftable) with a significance level of 0,043 < 0,05.